Resistance paste as well as preparation method and application thereof
By introducing Hf metal powder into the ruthenium oxide resistive slurry and adopting a specific group distribution ratio and preparation process, the problem of poor stability of the existing resistive slurry is solved, and the stability and performance of the resistive elements are significantly improved.
Patent Information
- Application Number
- CN202510227993.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-08
AI Technical Summary
The performance stability of existing ruthenium oxide (RuO2) resistive pastes is poor, especially after temperature changes and short-term overload, the performance of resistive components will decline.
Hf metal powder is introduced, and a resistive slurry composed of RuO2 powder, Hf metal powder, glass powder and organic carrier is prepared through specific component distribution ratios and preparation processes.
The performance stability of thick film resistive paste is significantly improved. The HTCR and CTCR of the prepared chip resistors have little changes, the encapsulation change rate is also small, and the stability is significantly improved.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of resistor pastes, and in particular relates to a resistor paste and a preparation method and application thereof. Background Art
[0002] Thick film resistor pastes are mostly composed of four parts: conductive phase, binder phase, modifier and organic carrier. Among them, thick film resistor pastes with ruthenium oxide (RuO2) as the conductive phase have good process repeatability, low sensitivity and can be sintered in the atmosphere, overcoming the process disadvantages of Ag-Pd resistor pastes. They have quickly occupied the thick film resistor paste market and become the most widely used thick film resistor paste. They are the preferred resistor paste for preparing high-performance MCM components.
[0003] However, the components of RuO2 resistor paste are complex, and the preparation process of related devices is complicated. The preparation of RuO2 powder, the selection of paste formula, the regulation of paste physical properties, screen printing process and firing process all have an important impact on the performance of the final resistor element. The preparation of high-quality resistor paste is the key to obtaining high-quality resistor elements. However, the performance of current resistor pastes is uneven and the stability is poor. After temperature changes and short-term overload, the performance deteriorates. Therefore, the development of ruthenium oxide resistor paste with stable performance is urgently needed. Summary of the invention
[0004] In order to further improve the performance stability of thick film resistor paste, the present invention provides a resistor paste, the components of the resistor paste are: 20-30 parts of RuO2 powder, 1-4 parts of Hf metal powder, 30-40 parts of glass powder, and 30-50 parts of organic carrier, by mass; the purity of the Hf metal powder is 99.99%, and the particle size is 50-70nm.
[0005] Furthermore, the components of the glass powder are: in mass percentage, 30% SiO2, 25% B2O3, 20% CaO, 10% Al2O3, 10% Na2O, and 5% IrO2.
[0006] Furthermore, the components of the organic carrier are: by mass percentage, 70-85% solvent and 15-30% resin; the solvent is selected from: one of terpineol, tributyl citrate, and butyl carbitol; the resin is selected from: one or more of polymethacrylic acid resin, epoxy thermosetting resin, and polyethylene wax.
[0007] On the other hand, the present invention also provides a method for preparing the resistor paste, including: preparing RuO2 powder, preparing glass powder, preparing an organic carrier, and preparing the resistor paste.
[0008] Specifically, RuO2 powder is prepared by hydrolyzing RuCl3, including: Prepare a RuCl3 solution with a concentration of 0.5-1.5 mol / L and a 1 mol / L NaOH solution; After heating the RuCl3 solution to 50-90°C, add 5wt% of dispersant under stirring. After sufficient stirring, uniformly add NaOH solution until black flocculent precipitate appears. Observe the pH value of the solution with a pH meter to make the pH value between 7 and 8, and then stop stirring. Keep warm for 10-15 minutes, remove the supernatant, and add deionized water to wash until the conductivity of the filtrate is less than 20μs / cm; Place the filter cake in a box-type high-temperature furnace, heat it up at a rate of 10°C / min, and keep it at 400-500°C for 30-60 min to obtain RuO2 powder.
[0009] In the preparation of RuO2 powder, the dispersant includes: PVP and ethylene glycol.
[0010] Specifically, the preparation method of glass powder includes: In terms of mass percentage, 30% SiO2, 25% B2O3, 20% CaO, 10% Al2O3, 10% Na2O, and 5% IrO2 were mixed in a ball mill for 30 min; Place the mixed powder in a platinum crucible, heat to 1200~1400℃ at a heating rate of 10~15℃ / min, and keep warm for 2~3h; Then quickly pour it into deionized water to obtain glass slag, dry it, put it in an agate jar with a ball-to-material ratio of 3:1, and wet-grind it in a planetary ball mill at a speed of 1000-1200 r / min with water as the medium for 8-10 hours, then filter and dry it.
[0011] Specifically, the preparation method of the organic carrier includes: In terms of mass percentage, 70-85% of the solvent and 15-30% of the resin are placed in a reaction kettle, and then the reaction kettle is placed in a homogeneous reactor, and kept at 80-90°C for 20-24 hours at a speed of 1400-1500 r / min to obtain a colorless transparent liquid; Add 3 wt % of a surfactant and 1 wt % of a thixotropic agent, stir in a water bath at 50-60° C. for 30-60 min, and prepare an organic carrier; The solvent is selected from: one of terpineol, tributyl citrate, and butyl carbitol; The resin is selected from: one or more of polymethacrylic acid resin, epoxy thermosetting resin, and polyethylene wax; The surfactant is Span 85, and the thixotropic agent is castor oil.
[0012] Specifically, the preparation method of the resistor paste includes: According to the above raw material ratio, weigh RuO2 powder, Hf metal powder and glass powder, and premix them by grinding, ball milling or ultrasonication for 30 minutes to obtain a mixture a; The prepared organic carrier is mixed with mixture a according to the raw material ratio, and secondary mixing is performed in a mixer at a speed of 1200-1600 r / min for 3-8 min; The slurry is rolled by a three-roller mill to a fineness of <15 μm and a viscosity of 125-145 Pa·s to obtain a finished resistor slurry.
[0013] Finally, the present invention claims protection for the use of the resistor paste in preparing thick film resistors.
[0014] Compared with the prior art, the present invention has at least the following beneficial effects or advantages: the present invention introduces Hf metal powder, which effectively improves the performance stability of the thick film resistor slurry, and the HTCR and CTCR of the prepared chip resistor change slightly (within 300 ppm), and the encapsulation change rate is small (less than 5%). The comparative example without adding Hf metal powder has large changes in HTCR and CTCR, large encapsulation change rate, and poor stability. DETAILED DESCRIPTION
[0015] The technical solution of the present invention is clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Example 1 This embodiment describes the preparation of thick film resistor paste, including: preparation of RuO2 powder, preparation of glass powder, preparation of organic carrier, and preparation of resistor paste.
[0017] 1) Preparation of RuO2 powder: prepare a RuCl3 solution with a concentration of 0.5 mol / L and a NaOH solution with a concentration of 1 mol / L; heat the RuCl3 solution to 50°C, add 5 wt% PVP (dispersant) under stirring, and after sufficient stirring, uniformly add NaOH solution until a black flocculent precipitate appears, observe the pH value of the solution with a pH meter, and make the pH value between 7 and 8, then stop stirring; continue to keep warm for 10 minutes, then remove the supernatant, add deionized water to wash until the conductivity of the filtrate is less than 20 μs / cm; place the filter cake in a box-type high-temperature furnace, heat at a rate of 10°C / min, and keep warm at 430°C for 60 minutes to obtain RuO2 powder.
[0018] 2) Preparation of glass powder: The raw material components of the glass powder (in terms of mass percentage, 30% SiO2, 25% B2O3, 20% CaO, 10% Al2O3, 10% Na2O, and 5% IrO2) were mixed in a ball mill for 30 minutes; the mixed powder was placed in a platinum crucible, heated to 1200°C at a heating rate of 10°C / min, and kept warm for 3 hours, and then the melt was quickly poured into deionized water to obtain glass slag; it was dried and placed in an agate jar at a ball-to-material ratio of 3:1, and wet-milled in a planetary ball mill at a speed of 1000 r / min with water as the medium for 10 hours, then filtered and dried.
[0019] 3) Preparation of organic carrier: 70% pineol (solvent) and 30% polymethacrylate resin (resin) were weighed in mass percentage and placed in a reactor, and then the reactor was placed in a homogeneous reactor, and kept at 80°C for 24 hours at a speed of 1400 r / min to obtain a colorless transparent liquid; 3wt% Span 85 (surfactant) and 1wt% castor oil (thixotropic agent) were added, and stirred in a 50°C water bath for 60 minutes to obtain an organic carrier.
[0020] 4) Preparation of resistor slurry: Weigh 20 g of the prepared RuO2 powder, 1 g of Hf metal powder (purity of 99.99%, particle size of 50-70 nm), and 30 g of glass powder, and premix them by ultrasonic for 30 min to obtain a mixture a; mix 30 g of the prepared organic carrier with the mixture a, and perform secondary mixing in a mixer at a speed of 1200 r / min for 8 min; use a three-roll mill to roll the slurry to a fineness of <15 μm and a viscosity of 125-145 Pa·s to obtain a finished resistor slurry.
[0021] Example 2 This embodiment describes the preparation of thick film resistor paste, including: preparation of RuO2 powder, preparation of glass powder, preparation of organic carrier, and preparation of resistor paste.
[0022] 1) Preparation of RuO2 powder: prepare a RuCl3 solution with a concentration of 1 mol / L and a NaOH solution with a concentration of 1 mol / L; heat the RuCl3 solution to 70°C, add 5 wt% PVP (dispersant) under stirring, and after sufficient stirring, uniformly add NaOH solution until a black flocculent precipitate appears, observe the pH value of the solution with a pH meter, and make the pH value between 7 and 8, then stop stirring; continue to keep warm for 12 minutes, then remove the supernatant, add deionized water to wash until the conductivity of the filtrate is less than 20 μs / cm; place the filter cake in a box-type high-temperature furnace, heat at a rate of 10°C / min, and keep warm at 450°C for 40 minutes to obtain RuO2 powder.
[0023] 2) Preparation of glass powder: The raw material components of the glass powder (in terms of mass percentage, 30% SiO2, 25% B2O3, 20% CaO, 10% Al2O3, 10% Na2O, and 5% IrO2) were mixed in a ball mill for 30 minutes; the mixed powder was placed in a platinum crucible, heated to 1300°C at a heating rate of 12°C / min, and kept warm for 2.5 hours, and then the melt was quickly poured into deionized water to obtain glass slag; it was dried and placed in an agate jar at a ball-to-material ratio of 3:1, and wet-milled in a planetary ball mill at a speed of 1100 r / min with water as the medium for 9 hours, then filtered and dried.
[0024] 3) Preparation of organic carrier: 80% tributyl citrate (solvent) and 20% epoxy thermosetting resin (resin) were weighed in mass percentage and placed in a reaction kettle, and then the reaction kettle was placed in a homogeneous reactor, and kept at 85°C for 22 hours at a speed of 1450 r / min to obtain a colorless transparent liquid; 3wt% Span 85 (surfactant) and 1wt% castor oil (thixotropic agent) were added, and stirred in a 55°C water bath for 40 minutes to obtain an organic carrier.
[0025] 4) Preparation of resistor slurry: Weigh 25 g of the prepared RuO2 powder, 2 g of Hf metal powder (purity of 99.99%, particle size of 50-70 nm), and 35 g of glass powder, and premix them by ultrasonic for 30 min to obtain a mixture a; mix 40 g of the prepared organic carrier with the mixture a, and perform secondary mixing in a mixer at a speed of 1400 r / min for 6 min; use a three-roll mill to roll the slurry to a fineness of <15 μm and a viscosity of 125-145 Pa·s to obtain a finished resistor slurry.
[0026] Example 3 This embodiment describes the preparation of thick film resistor paste, including: preparation of RuO2 powder, preparation of glass powder, preparation of organic carrier, and preparation of resistor paste.
[0027] 1) Preparation of RuO2 powder: prepare a RuCl3 solution with a concentration of 1.5 mol / L and a NaOH solution with a concentration of 1 mol / L; heat the RuCl3 solution to 90°C, add 5 wt% ethylene glycol (dispersant) while stirring, and after sufficient stirring, uniformly add NaOH solution until a black flocculent precipitate appears, observe the pH value of the solution with a pH meter, and make the pH value between 7 and 8, then stop stirring; continue to keep warm for 15 minutes, then remove the supernatant, add deionized water to wash until the conductivity of the filtrate is less than 20 μs / cm; place the filter cake in a box-type high-temperature furnace, heat at a rate of 10°C / min, and keep warm at 500°C for 30 minutes to obtain RuO2 powder.
[0028] 2) Preparation of glass powder: The raw material components of the glass powder (in terms of mass percentage, 30% SiO2, 25% B2O3, 20% CaO, 10% Al2O3, 10% Na2O, and 5% IrO2) were mixed in a ball mill for 30 minutes; the mixed powder was placed in a platinum crucible, heated to 1400°C at a heating rate of 15°C / min, and kept warm for 2 hours, and then the melt was quickly poured into deionized water to obtain glass slag; it was dried and placed in an agate jar at a ball-to-material ratio of 3:1, and wet-milled in a planetary ball mill at a speed of 1200 r / min with water as the medium for 8 hours, then filtered and dried.
[0029] 3) Preparation of organic carrier: 85% butyl carbitol (solvent) and 15% polyethylene wax (resin) were weighed in mass percentage and placed in a reactor, and then the reactor was placed in a homogeneous reactor, and kept at 90°C for 20 hours at a speed of 1500 r / min to obtain a colorless transparent liquid; 3wt% Span 85 (surfactant) and 1wt% castor oil (thixotropic agent) were added, and stirred in a 60°C water bath for 30 minutes to obtain an organic carrier.
[0030] 4) Preparation of resistor slurry: weigh 30 g of the prepared RuO2 powder, 4 g of Hf metal powder (purity of 99.99%, particle size of 50-70 nm), and 40 g of glass powder, and pre-mix them by ball milling for 30 min to obtain a mixture a; mix 50 g of the prepared organic carrier with the mixture a, and perform secondary mixing in a mixer at a speed of 1600 r / min for 3 min; use a three-roll mill to roll the slurry to a fineness of <15 μm and a viscosity of 125-145 Pa·s to obtain a finished resistor slurry.
[0031] Comparative Example 1 This example describes the preparation of thick film resistor paste without adding Hf metal powder.
[0032] The preparation method of the thick film resistor slurry is the same as that of Example 1, except that no Hf metal powder is added.
[0033] Comparative Example 2 This example describes the preparation of thick film resistor paste without adding Hf metal powder.
[0034] The preparation method of the thick film resistor paste is the same as that of Example 2, except that no Hf metal powder is added.
[0035] Comparative Example 3 This example describes the preparation of thick film resistor paste without adding Hf metal powder.
[0036] The preparation method of the thick film resistor paste is the same as that of Example 3, except that no Hf metal powder is added.
[0037] Example 4 This embodiment describes the performance test of the thick film resistor pastes prepared in Examples 1-3 and Comparative Examples 1-3.
[0038] The resistor pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were screen printed, left to level, dried at 150°C for 10 min, and sintered in a tunnel furnace at a peak temperature of 850°C, a duration of 10 min, a heating time of 30 min, and a cooling time of 20 min to obtain chip resistor samples. The samples were tested for performance, and the average value of three samples in each group was taken. The test pattern used a 1mm×1mm pattern. The specific test method is as follows: 1) Viscosity: Viscosity is the most important parameter to characterize the rheological properties of resistor slurry, and is measured using a viscometer. Anton Paar's MCR302 viscometer is used to test the viscosity of the slurry, and the rotating rod speed is set to 10r / min.
[0039] 2) Fineness: The fineness of resistor slurry refers to the coarseness of the solid particles in the slurry. It is an important parameter to characterize the uniformity of the slurry and is measured using a scraper fineness meter.
[0040] 3) Sintering film thickness: Tunnel furnace sintering in atmospheric atmosphere, peak temperature 850±5℃, peak time 9~11min.
[0041] 4) Resistance: Select the appropriate range of the resistance meter, connect the two test leads to the electrodes at both ends of the resistance to be measured, and record the value and unit.
[0042] 5) Temperature coefficient: Positive temperature coefficient (HTCR) test method: Set the test equipment temperature to 25℃, wait for the temperature to stabilize, measure the resistance value to be R1, and record it. Set the test equipment temperature to 125℃, wait for the temperature to stabilize, measure the resistance value to be R2, and record it. Calculation formula: X (HTCR) = .
[0043] Negative temperature coefficient (CTCR) test method: Set the test equipment temperature to 25℃, wait for the temperature to stabilize, measure the resistance value to be R3, and record it. Set the test equipment temperature to -55℃, wait for the temperature to stabilize, measure the resistance value to be R4, and record it. Calculation formula: X (CTCR) = .
[0044] 6) Encapsulation change rate: To ensure the stability of the circuit, the general method is to sinter a layer of glass glaze protective film on the circuit surface. Use Hongxing I-5337 dielectric slurry to encapsulate the resistor slurry, sintering curve at 525℃, sintering at peak temperature for 5 minutes. The test results are shown in Table 1.
[0045] Table 1. Resistance slurry performance test data
[0046] The test results in Table 1 show that, in Examples 1 to 3, Hf metal powder is used as an additive to thick film resistor slurry, and the HTCR and CTCR of the prepared chip resistors vary slightly (within 300 ppm), and the encapsulation variation rate is even smaller (less than 5%). The HTCR and CTCR of the chip resistors prepared in the comparative example vary greatly, and the encapsulation variation rate is relatively large, indicating that the use of Hf metal powder in the present invention improves the performance stability of the resistor slurry.
[0047] The above embodiments can well illustrate the technical solutions of the present invention, but they are only descriptions of the preferred implementation modes of the present invention, and do not limit the scope of the present invention. Without departing from the design spirit of the present invention, various changes and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the protection scope determined by the present invention.
Claims
1. A resistor paste, characterized in that: The components of the resistor paste are: by mass, 20-30 parts of RuO2 powder, 1-4 parts of Hf metal powder, 30-40 parts of glass powder, and 30-50 parts of organic carrier; The purity of the Hf metal powder is 99.99% and the particle size is 50-70 nm.
2. The resistor paste according to claim 1, characterized in that: The components of the glass powder are: by mass percentage, 30% SiO2, 25% B2O3, 20% CaO, 10% Al2O3, 10% Na2O, and 5% IrO2.
3. The resistor paste according to claim 1, characterized in that: The components of the organic carrier are: by mass percentage, 70-85% solvent and 15-30% resin; The solvent is selected from: one of terpineol, tributyl citrate, and butyl carbitol; The resin is selected from: one or more of polymethacrylic resin, epoxy thermosetting resin, and polyethylene wax.
4. The method for preparing the resistor paste according to claim 1, characterized in that: include: Preparation of RuO2 powder, preparation of glass powder, preparation of organic carrier, preparation of resistor paste.
5. The preparation method according to claim 4, characterized in that: The RuO2 powder is prepared by hydrolyzing RuCl3, including: preparing a RuCl3 solution with a concentration of 0.5-1.5 mol / L and preparing a 1 mol / L NaOH solution; After heating the RuCl3 solution to 50-90°C, add 5wt% of dispersant under stirring. After sufficient stirring, uniformly add NaOH solution until black flocculent precipitate appears. Observe the pH value of the solution with a pH meter to make the pH value between 7 and 8, and then stop stirring. Keep warm for 10-15 minutes, remove the supernatant, and add deionized water to wash until the conductivity of the filtrate is less than 20μs / cm; Place the filter cake in a box-type high-temperature furnace, heat it up at a rate of 10°C / min, and keep it at 400-500°C for 30-60 min to obtain RuO2 powder.
6. The preparation method according to claim 5, characterized in that: The dispersant includes: PVP and ethylene glycol.
7. The preparation method according to claim 4, characterized in that: The preparation method of the glass powder includes: mixing 30% SiO2, 25% B2O3, 20% CaO, 10% Al2O3, 10% Na2O, and 5% IrO2 by mass percentage in a ball mill for 30 minutes; Place the mixed powder in a platinum crucible, heat to 1200~1400℃ at a heating rate of 10~15℃ / min, and keep warm for 2~3h; Then quickly pour it into deionized water to obtain glass slag, dry it, put it in an agate jar with a ball-to-material ratio of 3:1, and wet-grind it in a planetary ball mill at a speed of 1000-1200 r / min with water as the medium for 8-10 hours, then filter and dry it.
8. The preparation method according to claim 4, characterized in that: The preparation method of the organic carrier comprises: placing 70-85% of a solvent and 15-30% of a resin in a reaction kettle by mass percentage, then placing the reaction kettle in a homogeneous reactor, and keeping the temperature at 80-90° C. for 20-24 hours at a speed of 1400-1500 r / min to obtain a colorless transparent liquid; Add 3 wt % of a surfactant and 1 wt % of a thixotropic agent, stir in a water bath at 50-60° C. for 30-60 min, and prepare an organic carrier; The solvent is selected from: one of terpineol, tributyl citrate, and butyl carbitol; The resin is selected from: one or more of polymethacrylic acid resin, epoxy thermosetting resin, and polyethylene wax; The surfactant is Span 85, and the thixotropic agent is castor oil.
9. The preparation method according to claim 4, characterized in that: The preparation method of the resistor paste comprises: according to the raw material ratio in claim 1, weighing RuO2 powder, Hf metal powder and glass powder, and premixing them for 30 minutes by grinding, ball milling or ultrasonic premixing to obtain a mixture a; The prepared organic carrier is mixed with mixture a according to the raw material ratio, and secondary mixing is performed in a mixer at a speed of 1200-1600 r / min for 3-8 min; The slurry is rolled by a three-roller mill to a fineness of <15 μm and a viscosity of 125-145 Pa·s to obtain a finished resistor slurry.
10. Use of the resistor paste according to claim 1 in preparing thick film resistors.
Citation Information
Patent Citations
Silicon solar cell front silver electrode high-square-resistance slurry and manufacturing method thereof
CN103440897A
Resistance paste for high-stability thick-film resistor
CN113643869A
Lead-free thick-film resistor paste
CN114613529A
Thick film resistor composition and usage thereof
JP1990112202A
PTC element
JP2004303912A